Prevalence of single-nucleotide variants in twenty-five pharmacogenes from a Cuban sample cohort - Elizabeth Reyes-Reyes; Elizabeth Reyes-Reyes; José Alfredo Herrera-Isidrón; Elizabeth Cuétara-Lugo; Elizabeth Cuétara-Lugo; Zhiv Shkedy; Dirk Valkenborg; Claudina Angela Pérez-Novo; Gisselle Fernández-Peña; Idania González-Pérez; Miguel David Fernández-Pérez; Wim Vanden-Berghe; et al. (Frontiers in Pharmacology, 2024)
IntroductionThe Cuban population is genetically diverse, and information on the prevalence of genetic variants is still limited. As complex admixture processes have occurred, we hypothesized that the frequency of pharmacogenetic variants and drug responses may vary within the country. The aims of the study were to describe the frequency distribution of 43 single-nucleotide variants (SNVs) from 25 genes of pharmacogenetic interest within the Cuba population and in relation to other populations, while taking into consideration some descriptive variables such as place of birth and skin color.Materials and MethodsSNVs were analyzed in 357 unrelated healthy Cuban volunteers. Genotype, allele frequencies, and ancestry proportions were determined, and the pairwise fixation index (FST ) was evaluated.ResultsHardy–Weinberg equilibrium (HWE) deviations in six loci (rs11572103, rs2740574, rs776746, rs3025039, rs861539, and rs1762429) were identified. Minor allele frequencies (MAFs) ranged from 0.00 to 0.15 for variants in genes encoding xenobiotic metabolizing enzymes. They also ranged from 0.01 to 0.21 for variants in DNA repair, growth factors, methyltransferase, and methyl-binding proteins, while they ranged from 0.04 to 0.27 for variants in the O-6-methylguanine-DNA methyltransferase enzyme. Moderate genetic divergence was observed upon comparison to Africans (FST = 0.071 and SD 0.079), with 19 markers exhibiting moderate-to-large genetic differentiation. The average European, African, and Amerindian ancestry proportions were 67.8%, 27.2%, and 5.3%, respectively. Ancestry proportions differed by skin color and birthplace for both African and European components, with the exception of the European component, which showed no significant difference between individuals from Western and Eastern regions. Meanwhile, the statistical significance varied in comparisons by skin color and birthplace within the Amerindian component. Low genetic divergence was observed across geographical regions. We identified 12 variants showing moderate-to-large differentiation between White/Black individuals.ConclusionAltogether, our results may support national strategies for the introduction of pharmacogenetic tools in clinical practice, contributing to the development of precision medicine in Cuba.